IMPLEMENTASI TANGGUNG JAWAB PENGELOLA APOTIK TERHADAP KONSUMEN OBAT - Mig Irianto Legowo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
The pharmacy is a pharmacy or place of service where pharmacy practice is carried out by pharmacists. In accordance with the provisions of a pharmacist can establish a Pharmacy with its own capital and / or capital from a capital owner both individuals and companies. Furthermore, in the case of pharmacists who establish a pharmacy in collaboration with capital owners, the work of organizing mandatory pharmacy is still carried out entirely by the pharmacist in question, therefore the responsibility of the pharmacist is as the manager of the pharmacy, which raises responsibility for the drug consumers The businessman / manager of the pharmacy is also obliged to provide the right service and information to the drug consumers. This study entitled Implementation of the Responsibility of Pharmacy Management for Drug Consumers aims to (1) know the responsibility of the pharmacist / manager to consumers in providing medicines, (2 ) to find out the problems faced by businessmen / managers of pharmacies in carrying out their obligations to dru. The type of research used is normative juridical with research specifications that are descriptive analytical. In this study the data is obtained from secondary data as primary data and primary data as supporting data (complementary). While the data collection method is interviews for primary data and literature studies for secondary data. The data obtained is presented in the form of a description of the event and then analyzed by qualitative descriptive analysis. In the case of a Pharmacy committing a serious violation that is life-threatening, then the SIA sanction for a Pharmacist's License Letter can be revoked without prior warning. (2) problems of problems faced by employers or managers of pharmacies include (a) drugs that are no longer circulating (b) drugs that have expired, (c) supplies of medicines run out. Then the business carried out by the pharmacy entrepreneur is (a) the pharmacy gives substitute drugs that have the same use. (B) if the drug has expired the pharmacy will exchange the drug to PBF. (C) if the drug supply runs out the pharmacy will advise consumers to search the drug runs out to another pharmacy.